Quality of life improvements and clinical assessments in kidney transplant recipients undergoing pegloticase treatment for uncontrolled gout: findings of the phase 4 PROTECT clinical trial - Abdellatif, Abdul; Zhao, Lin; Obermeyer, Katie; Vranic, Zana; Marder, Brad A.; Scandling, John D. (Frontiers in Immunology, 2025)
IntroductionGout is 12-times more prevalent in kidney transplant (KT) recipients than in non-transplanted population. We report quality-of-life (QOL) and clinical assessment findings from the PROTECT trial examining pegloticase efficacy and safety in KT recipients with uncontrolled gout.MethodsPatients with serum urate (SU) ≥7 mg/dL, oral urate-lowering therapy refractory/intolerant, and with one of the following were enrolled: ≥2 flares/year, unresolving tophi, or chronic gouty arthritis. Patients were ≥1 year post-transplant, with a graft eGFR ≥15 ml/min/1.73m2 and received stable immunosuppression. Pegloticase was administered for 24 weeks. QOL endpoints included the Health Assessment Questionnaire (HAQ; Disability Index [DI], Health, Pain) and Physician Global Assessment (PhGA) of Gout. Key clinical assessments included proportion of patients with resolution of ≥1 tophus and change from baseline in blood pressure (BP) at Week 24.ResultsTwenty KT recipients (85.0% male, age: 53.9±10.9 years, BMI: 30.6±7.2 kg/m2, eGFR: 45.8±11.9 ml/min/1.73 m2, time since kidney transplant: 14.6±6.9 years) were included. The primary endpoint was achieved with 89% of patients reaching and maintaining a SU of <6 mg/dL during Month 6. Meaningful improvements occurred over 24 weeks of treatment in all QOL measures (mean [95% CI] change from baseline: HAQ-DI: -0.3 [-0.6, 0.1], HAQ-Pain: -35.5 [-54.5, -16.5], HAQ-Health: -22.4 [-39.5, -5.2], PhGA: -2.4 [-3.7, -1.1]) and clinical assessments (≥1 tophus resolved: 3 of 7 with tophi at baseline [42.9%]; change from baseline in mean arterial BP: -6.8 [-12.5, -1.0] mmHg).ConclusionsGiven the high prevalence of uncontrolled gout in KT recipients, proper SU management is of particular importance. Additionally, intensive urate-lowering with pegloticase may have clinical and QOL benefits.